Small GTPases and phosphoinositides in the regulatory mechanisms of macropinosome formation and maturation - Egami, Youhei; Taguchi, Tomohiko; Maekawa, Masashi; Arai, Hiroyuki; Araki, Nobukazu (Frontiers in Physiology, 2014)
Macropinosome formation requires the sequential activation of numerous signaling pathways that coordinate the actin-driven formation of plasma membrane protrusions (ruffles) and circular ruffles (macropinocytic cups), followed by the closure of these macropinocytic cups into macropinosomes. In the process of macropinosome formation, localized productions of phosphoinositides such as PI(4,5)P2 and PI(3,4,5)P3 spatiotemporally orchestrate actin polymerization and rearrangement through recruiting and activating a variety of actin-associated proteins. In addition, the sequential activation of small GTPases, which are known to be master regulators of the actin cytoskeleton, plays a pivotal role in parallel with phosphoinositides. To complete macropinosome formation, phosphoinositide breakdown and Rho GTPase deactivation must occur in appropriate timings. After the nascent macropinosomes are formed, phosphoinositides and several Rab GTPases control macropinosome maturation by regulating vesicle trafficking and membrane fusion. In this review, we summarize recent advances in our understanding of the critical functions of phosphoinositide metabolism and small GTPases in association with their downstream effectors in macropinocytosis.